Daylight in the swamp : memoirs of Selwyn Dewdney - Dewdney, Selwyn H. (Dundurn Press, 1997)
Daylight in the Swamp is the bush memoirs of Selwyn Dewdney, a noted Canadian artist and recorder of native rock art. His two great loves, art and the Canadian north, come together in this book. His respect for native culture and art is reflected in his own work, his insight into native rock art, and his passion for canoeing and the northern experience. The third theme of the book is history spanning the period from 1910 through to the 1970s during which the old north largely vanished. Dewdney was there to record the images of forgotten dreams painted on rocks and cliffs throughout the Canadian.